GERMAN-ROMANTISM LANGUAGE CULTURE - Yulian Evgenievich Grinivetskiy (Вестник Северо-Кавказского федерального университета)
The subject of this article is connected with a complex of the research directions actual for the modern humanities. It is analyzed a German language culture which differs an abundance of abstract names, updating of art concept-sphere, domination of the artist and the wanderer as person types, an abundance of lexical-semantic binary oppositions.